Total synthesis and biological studies of a new anti-proteasome drug, lactacystin and its derivatives / Ahmad Sazali Hamzah and Zurina Shaameri - Hamzah, Ahmad Sazali; Shaameri, Zurina (2005)
Lactacystin is the first non-protein metabolite isolated from Streptomyces specie by Omura in 1991. It mimics the nerve growth factor because it inhibits cell growth and induces neurite outgrowth. Since nerve growth factor is essential for the survival and function of nerve cells or neurons, lactacystin can be a suitable alternative in the therapy of neurodegenerative diseases like Alzheimer's and Parkinson's. Lactacystin possesses a common structural moiety, 3-hydroxy-4-methyl proline, which is also found in many biologically active natural products. This proline ring system, which derived from the basic pyrrolidine ring skeleton, can act as a versatile intermediate for synthesizing more complex medicinally important compounds such as piracetam, clausenamide, detoxine, tirandamycin and echinocandin. This work reports on the synthesis of a pyrrolidine-ring template, β,β-diketoester, and the use of it as a building block to synthesize lactacystin and some other biologically active compounds. By means of various synthetic methods, over 40 compounds with the pyrrolidine ring system have been generated in fairly good yields. Some were found to exhibit neuroprotective ability via the hydrogen peroxide oxidative stress-induced model. Identification of important partial structures such as above can lead to the discovery of a new drug with potential medicinal values.